Prospect and potentiality of finger millet in Nepal: Nutritional security and trade perspective - Gairhe, Samaya; Gauchan, Devendra; Timsina, Krishna Prasad (Journal of Agriculture and Natural Resources, 2021)
Millet is an important food crop for ensuring food and nutrition security of smallholder farmers and marginalized communities in the hill and mountain of Nepal. The main objectives of the study were to assess prospects and potentiality of millet by analysing the area, production, productivity, and trade for the year 2009-2019. The study used a combination of exploratory survey and secondary data for assessing the production system, compound growth rate, coefficient of variation (CV), instability index (IIN), and trade specialization index. The results of the study are compiled and the synthesis of the analysis is presented in both tabular and graphic forms. Growth rate analysis showed that the area of millet is declining but the import value, production, and yield were increasing at the rate of 14.62, 0.47, and 0.73 percent per annum respectively. Import and export values and quantity showed higher CV as well as IIN while area, production, and yield showed lower values. The trade specialization index was found as -0.992, which indicates that millet is in the introduction phase. Out of the total millets area, 78% of the area lies in the hill, 19% in the mountain, and only 3% in the terai. The highest area and production can be observed in Bagmati province while the least was observed in province no two. The study implies that there is a need to increase production and productivity to reduce increasing imports and make the country self-reliant in millet production with increased investment in research and development and adequate support from national policies and programs.